Museums: An institution for knowledge acquisition – A spotlight on the museum education in Ghana (International Journal of Technology and Management Research, 2020)
Museums, just like formal institutions of learning always have understood that conserving collections for study and exhibition can be an important part of the educational process. Since 1957, Ghana has established several museums under the Museums and Monument Board. These museums just like others are required to play a great deal of role in the social, educational, economic development of a nation. However, it is distressing to note that with the highly endowed museum assets of Ghana, such as the Cape Coast Castle Museum, Ghana National Museum, Fort Appolonia Museum of Nzema History and Culture, the Elmina Castle Museum, Ho Museum, Bolga Museum, Wa Museum, The Head of State Museum and Museum of Science and Technology both in Accra, there has been little contributions to Ghana’s Gross Domestic Product. Significantly, visitor experience and satisfaction is very low. In this view, this study sought to investigate educational activities of Ghana Museum and Monument Board (GMMB) and inquire into their educational activities. Employing qualitative approaches, the study used a triangulation of observations, interview and focus group discussion to assemble data from these museums. In conclusion, the museums provide some sort of education but there is no formalized educational framework serving as a guide. They mainly employ monotonous experience of guided and self-guided gallery tours, and occasionally, the museum curators and educators organize a oneoff programme such as an outreach to schools and special exhibitions as well as seminars. Recommendations to strengthening museum education in Ghana are addressedCitation: Kwasi Amoako – Ohene, Nana Ama Pokua Arthur, and Samuel Nortey.Museums: An institution for knowledge acquisition – A spotlight on the museum education in Ghana, 2020 5 (2): 10－23. Received: March 3, 2020 Accepted: June 30, 2020
Keywords: museum education; GMMB; visitor experience; exhibition; educational framework